Polyfluoroalkyl compounds in the marine environment – Investigations on their distribution in surface water and temporal trends in harbor seals (phoca vitulina) ... : Polyfluorierte Alkylverbindungen in der marinen Umwelt - Untersuchung zur Verteilung im Wasser und zeitlichen Trends in Seehunden (phoca vitulina) ... - Ahrens, Lutz (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2010)
Recently polyfluoroalkyl compounds (PFCs) were discovered as emerging persistentorganic pollutants. Because of their unique physicochemical properties due to theircombination of lipophilic and hydrophilic characteristics, PFCs have been widely used inmany consumer products, such as polymerisation aids, stain repellents on carpets, textiles, andpaper products for over 50 years. From the production and use of these products, PFCs can bereleased into the environment. Scientific concern about PFCs increased due to their globaldistribution and ubiquitous detection in the environment, especially in marine mammals.An analytical protocol was developed for the analysis of PFCs in water samples andvarious biological matrices. The samples were analysed for 40 PFCs plus 20 isotope-labelledinternal standards using high performance liquid chromatography/negative electrosprayionisation-tandem mass spectrometry (HPLC/(-)ESI-MS/MS). Furthermore, the analyticalquality of the laboratory has been approved in interlaboratory ...